Analisis Campuran Gypsum Dan Kapur Terhadap CBR Dan Permeabilitas Tanah Lempung - Kristina, Desi; Abduh, M. Natsir; Setiawan, Arman (Jurnal Penelitian Teknik Sipil Konsolidasi, 2025)
Soil improvement is needed to increase the soil's load-bearing capacity, one method being chemical stabilization using materials like gypsum and lime. Gypsum enhances soil stability due to its calcium content, which binds soil particles and reduces cracking. Lime strengthens the soil and reduces settlement by forming hydrates and minimizing capillary absorption. The goal of soil improvement is to bind and consolidate aggregate materials within the soil. Therefore, soil improvement using gypsum and lime is necessary for enhanced load-bearing capacity. In this study, CBR (California Bearing Ratio) and permeability tests were conducted with a gypsum substitution of 8% in each sample, and lime added at 15%, 20%, and 25%. The CBR and permeability values increased progressively. The original soil's CBR value was 16.15%, while soil mixed with gypsum showed values of 22.19%, 33.95%, 46.79%, and 53.06%, with a maximum increase of 53.00%. For permeability, the original soil had a rate of 0.0034%, and soil mixed with gypsum and lime showed rates of 0.0048%, 0.0057%, 0.0066%, and 0.0085%, with a maximum increase of 0.4117%.